Modelagem molecular do receptor canabinoide tipo-1 do papagaio-verdadeiro (Amazona aestiva): análise dos modos de acoplamento de fitocanabinoides - Santos Júnior, Elpídio Vicente dos (2025)
The cannabinoid type-1 receptor (CB1) has received increasing attention from the scientific community due to its central role in maintaining homeostasis, particularly for its pharmacological functions in the nervous and immune systems. Present in all vertebrates, CB1 is also attracting interest due to the therapeutic potential of secondary metabolites from Cannabis sativa (Linnaeus, 1753), whose ligands exhibit high affinity for the canonical binding site, stimulating the development of drugs aimed at modulating the endocannabinoid system, including potential applications in wild bird medicine. In this study, a three-dimensional model of the CB1 receptor from Amazona aestiva (Linnaeus, 1758), a South American parrot species whose experimental structure has not yet been elucidated, was constructed. Thus, the target receptor was obtained by homology, refined in membranes using 500-ns molecular dynamics simulations with GROMACS, and used in the virtual screening of several C. sativa secondary metabolites compiled from the literature (567 compounds from de plant, plus the reference agonist). Molecular docking was performed in the receptor active site using the GOLD genetic algorithm, using the full agonist CP55,940 as a control. The results showed that cannabisins, the ten variants tested, exhibited a high tendency to interact with the CB1 receptor, surpassing even the reference ligand CP55,940. The model also predicted high affinity for cannabisol, a dimeric phytocannabinoid derived from Δ9-tetrahydrocannabinol, recognized for its potent CB1 agonist activity. Another relevant finding was cannabitwinol, a cannabidiol dimer associated with thermoregulatory receptors, whose high affinity suggests possible bivalent activity, expanding theoretical hypotheses about its mechanisms of action. Finally, this study highlights the applicability of in silico approaches in the screening and prioritization of promising drug candidates selective for CB1 from A. aestiva, providing support for experimental investigations into the pharmacological relevance of C. sativa metabolites in wild birds.